The challenges of missionary activity after April 25: considerations and perspectives in Nigrizia - Enea, Eugenio (Lusitania sacra, 2025)
This contribution extends the final chapter of my doctoral thesis on the relations between the Holy See and Portugal (1926-1974), focusing on the expulsion of the missionaries and the Bishop of Nampula following the drafting and circulation of the document Um Imperativo de Consciência. In detail, the following pages report on the reflections of the Comboni missionaries in the magazine Nigrizia between 1974 and 1976. These reflections address the difficult post-colonial transition and the challenges faced by the Catholic Church in the newly independent countries, which were influenced by previous links with the colonial regime through the Missionary Agreement.